Is the benefit of using adjuvant capecitabine in patients with residual triple-negative breast cancer related to pathological response to neoadjuvant chemotherapy - ARIKAN, RUKİYE (My University, 2022)
Background Triple-negative-breast-cancer (TNBC) has a poor prognosis if pathologic complete response (pCR) cannot be achieved following neoadjuvant chemotherapy (NAC). The group of patients that benefit most from adjuvant capecitabine remains unclear. Materials and Methods We analyzed data of 160 consecutive patients with residual TNBC from eight cancer-center. Pathologic response was defined into two groups as having good-pathologic-response (MillerPayneGrading (MPG) IV-III) or poor-pathologic-response (MPG I-II). The characteristics of patients were compared regarding adjuvant capecitabine usage. Results Univariate-analysis revealed that age, histology, clinical-stage, tumor-size, lymph-nodes number, menopausal status, and pathological-stage were significantly different between two groups. In multivariate-analysis, menopausal status (p = 0.043) and residual tumor-size (p < 0.001) were found to be independent prognostic factors for pathological response. The hazard-ratio for disease recurrence and death in the poor-response group with adjuvant capecitabine was 2.94 (95% confidence-interval (CI), 1.21 to 7.10; p = 0.016) and 4.080 (95% CI, 1.22 to 13.64; p = 0.022), respectively. DFS (p = 0.58) and OS (p = 0.89) improvements with adjuvant capecitabine were not demonstrated in good-response groups. Conclusion This multicenter-study suggested that only the poor-response group to NAC achieved benefit from adjuvant capecitabine. Postmenopausal status and residual tumor-size were related to poor prognosis.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Onkoloji; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Oncology; ONKOLOJİ; Klinik Tıp; Klinik Tıp (MED); ONCOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Triple negative breast cancer; neoadjuvant chemotherapy response; pathological response; residual tumor size; adjuvant capecitabine; CYCLOPHOSPHAMIDE; EPIRUBICIN; DOCETAXEL